2015
DOI: 10.1111/1556-4029.12654
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Colored Acrylic, Cotton, and Wool Textile Fibers Using Micro‐Raman Spectroscopy. Part 2: Comparison with the Traditional Methods of Fiber Examination

Abstract: In the second part of this survey, the ability of micro-Raman spectroscopy to discriminate 180 fiber samples of blue, black, and red cottons, wools, and acrylics was compared to that gathered with the traditional methods for the examination of textile fibers in a forensic context (including light microscopy methods, UV-vis microspectrophotometry and thin-layer chromatography). This study shows that the Raman technique plays a complementary and useful role to obtain further discriminations after the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
2
15
0
2
Order By: Relevance
“…They demonstrated that the ability to obtain viable spectra significantly depended upon the laser wavelength used for analysis as well as the color and type of fiber . The second portion of this two‐part survey compared the results of analyzing 180 black, blue, and red cotton, wool, and acrylic fibers using Raman microspectroscopy with traditional methods including light microscopy, TLC, and UV–vis MSP . Raman spectroscopy is typically used to analyze the dyes in fibers and it was shown that by using four different wavelengths (i.e.…”
Section: Trace Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that the ability to obtain viable spectra significantly depended upon the laser wavelength used for analysis as well as the color and type of fiber . The second portion of this two‐part survey compared the results of analyzing 180 black, blue, and red cotton, wool, and acrylic fibers using Raman microspectroscopy with traditional methods including light microscopy, TLC, and UV–vis MSP . Raman spectroscopy is typically used to analyze the dyes in fibers and it was shown that by using four different wavelengths (i.e.…”
Section: Trace Evidencementioning
confidence: 99%
“…[92] The second portion of this two-part survey compared the results of analyzing 180 black, blue, and red cotton, wool, and acrylic fibers using Raman microspectroscopy with traditional methods including light microscopy, TLC, and UV-vis MSP. [93] Raman spectroscopy is typically used to analyze the dyes in fibers and it was shown that by using four different wavelengths (i.e. 514.5, 632.8, 785, and 830 nm), components in dye mixtures could be elucidated; where in some cases this was not achievable by other methods.…”
Section: Fibersmentioning
confidence: 99%
“…This technique is a nondestructive analysis, it needs no sample preparation, and the sample size can be in the order of picograms. Recently, Raman spectroscopy has been shown to be an effective multipurpose analytical method for forensic applications: identification of drugs [3], lipsticks [4], fibers [5], paints [6], and ink [7]. A previous study reported the identification of body fluids using Raman spectroscopy [8].…”
Section: Introductionmentioning
confidence: 99%
“…This allows color analysis to be performed directly on a sample mounted for microscopic examination without needing to remove the dye for a solution-based measurement [8]. MSP has been shown to have a high discriminatory power for differentiating between colored fibers, especially when the UV range is included in the analysis [4], [6]–[9], [12]. …”
Section: Introductionmentioning
confidence: 99%